Numerical Algorithm for Solving Market Clearing Problem in Power Electronics-Based Power Distribution Systems - Musharrat Sabah; Aaron M. Cramer; Yuan Liao (IEEE Open Access Journal of Power and Energy)
Market-based control is a control approach that can be used to organize resource control problems by establishing an artificial market economy for the allocation of these resources. In such system, the set of market-clearing prices is the set of prices that result in an equilibrium between demanded and supplied resources throughout the system. In this paper, a new method has been proposed for solving the market-clearing problem, the problem of determining the market-clearing prices. The algorithm is applied on a complex representative power system and three simplified power systems based on the representative system under different operational scenarios. The proposed method is compared with existing reference root-finding algorithms. The comparison illustrates the proposed algorithm’s ability to address the numerical challenges the market-clearing problem poses. Dynamic simulation has been used to demonstrate the efficacy of the proposed algorithm in clearing the market in a wide range of dynamic conditions.